Incidence of Cushing’s Disease in the Republic of North Macedonia for the period from 2013 to 2020, according to data derived from the national health system. - Jovanovska Mishevska, Sasha; Zhivkovic Hristova, Marija; Mucha, Argjent; Volkanovska Ilijevska, Cvetanka; Stevchevska, Aleksandra; Adamova, Katerina; Mladenovska, Ivana; Shubevska Stratova, Slavica (University Clinic of Endocrinology, Diabetes and Metabolic Disorders, Medical Faculty, University “Ss. Cyril and Methodius” - Skopje, 2022)
Cushing’s disease is a rare endocrine disorder characterized by increased secretion of adrenocorticotrophic hormone (ACTH) by a corticotropic pituitary adenoma. In our country there are no data on the incidence of Cushing’s disease and only sporadic case report have been published. Aim: To find the annual incidence rates of Cushing’s disease in the Republic of North Macedonia for the period from 2013 to 2020, based on data derived from the National eHealth System. Methods: The National eHealth System was searched for all patients with ICD-10 diagnosis E24.0 in their electronic healthcare records. The annual incidence rate of Cushing’s disease was estimated per 106 persons, according to the initial occurrence of the diagnosis. The National Data records from State Statistical Office (MAKSTAT) for the population per year were used. Results: The number of newly diagnosed registered cases with Cushing’s disease was 3 in year 2013, 4 in 2014, 5 in 2015, 2 in 2016, 4 in 2017, 4 in 2018 and there were no new cases diagnosed in 2019 and 2020. Compared to the registered number of citizens by years, the annual incidence rate of Cushing’s disease was 1.45 per one million for 2013; 1.93 /106 for 2014; 2.4/106 for 2015; 0.96 /106 for 2016; 1.93 /106 for 2017 and 1.92 /106 for 2018. The average annual incidence rate for Cushing’s disease was 1.77 cases per 100000 inhabitants. Conclusion: The worldwide incidence rate of Cushing’s disease is 1.2-2.4 cases in a million. The average annual incidence rate in our country corresponds to the reported global incidence.
Keywords: Cushing's disease